Pelaksanaan Tugas Guru di Sekolah Menengah Kejuruan Negeri Se-Kota Padang - Utami, Suchi; Sulastri, Sulastri (ARZUSIN, 2023)
This research is motivated by the results of observations conducted by the author during observations at the State Vocational High School (SMK Negeri) in Padang City, which showed indications of the suboptimal implementation of teacher duties. The aim of this research is to obtain data and information regarding how well the teacher duties are carried out at the State Vocational High School in Padang City, as seen from several aspects: 1) lesson planning, 2) lesson delivery, 3) assessment of learning outcomes, and 4) implementation of follow-up programs. Therefore, the problem to be addressed in this research is, "How well is the implementation of teacher duties at the State Vocational High School in Padang City?" This research is a quantitative descriptive study with a research population of 677 teachers. The sample size was determined using the Slovin formula with a 10% margin of error, and the Proportionate Stratified Random Sampling technique resulted in 110 teachers as the research sample. The data processing revealed that, for the implementation of teacher duties in lesson planning, the average score was 4.28 with a Total Category Rate (TCR) of 85.5%, which falls into the "good" category. For the implementation of teacher duties in lesson delivery, the average score was 4.25 with a TCR of 85.1%, also falling into the "good" category. In assessing learning outcomes, the average score was 3.89 with a TCR of 77.8%, which is considered "fairly good." The implementation of teacher duties in carrying out follow-up programs received an average score of 3.82 with a TCR of 76.5%, placing it in the "fairly good" category. The overall average score is 4.06, with a TCR of 81.2%, indicating a "good" category. In conclusion, the implementation of teacher duties at the State Vocational High School in Padang City is considered "good."